"Facebocrastination"? Predictors of using Facebook for procrastination and its effects on students' well-being. (November 2016) - Meier, Adrian; Reinecke, Leonard; Meltzer, Christine E.
Abstract: Procrastinating with popular online media such as Facebook has been suggested to impair users' well-being, particularly among students. Building on recent procrastination, self-control, and communication literature, we conducted two studies (total N  = 699) that examined the predictors of procrastination with Facebook as well as its effects on students' academic and overall well-being. Results from both studies consistently indicate that low trait self-control, habitual Facebook checking, and high enjoyment of Facebook use predict almost 40 percent of the variance of using Facebook for procrastination. Moreover, results from Study 2 underline that using Facebook for the irrational delay of important tasks increases students' academic stress levels and contributes to the negative well-being effects of Facebook use beyond the academic domain. The implications of investigating procrastination as a specific pattern of uncontrolled and dysfunctional media use are discussed with regard to research on the uses and effects of ubiquitous online media. Highlights: Using Facebook (FB) to procrastinate tasks is common among students. Trait self-control (TSC), FB habits, and FB enjoyment predicted procrastination. Procrastination with FB increased students' academic stress and FB-induced strains. Procrastination mediated the effects of TSC, habits, and enjoyment on well-being. Conclusion: Procrastinating with FB can impair users' well-being.